2019
DOI: 10.1097/sla.0000000000002435
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence Patterns and Long-term Results After Induction Chemotherapy, Chemoradiotherapy, and Curative Surgery in Patients With Locally Advanced Esophageal Cancer

Abstract: After curative surgery in a multimodal setting, the histological type and the response to neoadjuvant therapy predicted the time frame of relapse; this knowledge may influence further follow-up guidelines for esophageal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 12 publications
3
28
0
1
Order By: Relevance
“…Through tumor downsizing and downstaging, nCRT improves locoregional control and overall survival rates compared to surgery alone [2][3][4]. The degree of tumor regression in response to nCRT is directly related to long-term survival, with pathologic complete response (pCR) resulting in the most favorable long-term prognosis [4,5]. A pCR, defined as the absence of viable tumor cells at the site of the primary tumor after nCRT, is observed in around 16-29% of the patients after nCRT [2,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Through tumor downsizing and downstaging, nCRT improves locoregional control and overall survival rates compared to surgery alone [2][3][4]. The degree of tumor regression in response to nCRT is directly related to long-term survival, with pathologic complete response (pCR) resulting in the most favorable long-term prognosis [4,5]. A pCR, defined as the absence of viable tumor cells at the site of the primary tumor after nCRT, is observed in around 16-29% of the patients after nCRT [2,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with residual tumor cells after neoadjuvant therapy primarily experience relapse within the first two postoperative years; however, there have been reports of patients with complete remission who experienced late relapses four years after surgery. After curative surgery in a trimodality, the histological type and response to neoadjuvant therapy predicted different prognoses . The CROSS trial demonstrated median overall survival (OS) of 49.4 months in the nCRT + surgery group compared to 24 months in the surgery alone cohort ( P = 0.003) .…”
Section: Introductionmentioning
confidence: 99%
“…After curative surgery in a trimodality, the histological type and response to neoadjuvant therapy predicted different prognoses. 8 The CROSS trial demonstrated median overall survival (OS) of 49.4 months in the nCRT + surgery group compared to 24 months in the surgery alone cohort (P = 0.003). 9,10 The five-year survival rates were 47% and 34%, respectively, and 29% of patients reached a pathological complete response (pCR).…”
Section: Introductionmentioning
confidence: 99%
“…Over the decades, esophagectomy with lymph node (LN) dissection has remained the most effective treatment modality for patients with early-stage ESCC (6,7). Adequate lymph nodes harvested, esophagectomy might increase postoperative morbidity and mortality which is probably unsuitable for patients with suspected T1N0M0 disease (8)(9)(10).…”
Section: Bcakgroundmentioning
confidence: 99%